Estimating the Percentage of Lead in Different Types of Pottery Dinnerware Used in Libyan Home - Afaf A. H. Abumhdi; Abuojaylah A. Abdulmalik; Maruwan A. Alarbash; Safa M. Abraheem (African Journal of Advanced Pure and Applied Sciences, 2024)
Many people have long used ceramics to make dishes and utensils needed to prepare and cook food, and these colorful ceramic utensils used for eating are a source of lead poisoning. The current study aimed to disclose the amount of lead in the colors used to paint ceramic dinnerware in the Libyan home. In this study, dissolved lead was estimated from pottery utensils manufactured locally in Libya and imported from Tunisia and China for comparison, using a 4% acetic acid solution by volume. Through the results of the analysis of lead released in the acid solution from 18 samples of ceramic vessels, the results showed that the concentrations of total lead released in locally manufactured ceramic vessels ranged between (0.204 - 1.968) μg/ml. These results came within the range of values allowed by the US Food and Drug Administration as well as the International Evaluation Organization. The concentration of dissolved lead in ceramic utensils imported from Tunisia and China ranged between (0.223 - 2.160) μg/ml and (0.0124 - 3.597) μg/ml, respectively. These values are higher than those allowed internationally, which must not exceed 2.2 parts per million. The amount of lead dissolved in these utensils is directly proportional to the increase in its concentration. In the paints used, in addition to increasing the colors that contain it, which are red, green, white, and pink. In general, the concentration of lead released from locally manufactured ceramic utensils is lower than ceramic utensils imported from Tunisia and China, which must not exceed internationally permissible limits.